Mine Waste Dump Optimisation Based on Carbon Footprint - Tobgay, Namgyel Sithup (Curtin University, 2024)
Modern open-pit mining operations focus on maximizing net present value (NPV) while reducing haulage cost and carbon emissions. This study utilizes Mixed Integer Programming (MIP) to optimize net present value and minimize carbon footprints during production and waste dump scheduling. It proposes three MIP models to enhance haulage and carbon cost minimization, using exact haulage distances for more accurate cost assessments, potentially redefining mine scheduling and waste dump management.